Удмуртские народные сказки - Кралина Надежда Петровна (Удмуртия, 2016)
Экземпляры: аб. ЦБ (2017.04.05) / Инвентарный номер: 3139 / Цена: / Сис.шифр: 82.3(2Рос=Удм) / Авт.знак: У 30 / ГРНТИ: 17.71 / ББК: 82.3(2Рос=Удм)